Content Marketing, Brand Awareness, and Online Customer Review on Housewives’ Purchase Intention on Shopee - Riyadini, Nikita Gabby; Krisnawati, Wenti (Interdisciplinary Social Studies, 2022)
This research aims to find out the influence of Content Marketing, Brand Awareness, and Online Customer reviews on Purchase Intention on Housewives (IRT) in Shopee E-Commerce. The study used a sample of 107 respondents, the type of data used is primary and secondary. The purpose of this study was to find out the influence of Content Marketing, Brand Awareness, and Online Customer reviews on Purchase Intention on Housewives (IRT) using multiple linear regression analysis methods using the SPSS 20 program. The results showed that content marketing variables have a positive and significant effect on purchase intention, brand awareness has a positive and significant effect on purchase intention and online customer review has a positive and significant effect on purchase intention.